Covid‐19 vaccination BNT162b2 temporarily impairs semen concentration and total motile count among semen donors. (27th June 2022) - Gat, Itai; Kedem, Alon; Dviri, Michal; Umanski, Ana; Levi, Matan; Hourvitz, Ariel; Baum, Micha
Abstract: Background: The development of covid‐19 vaccinations represents a notable scientific achievement. Nevertheless, concerns have been raised regarding their possible detrimental impact on male fertility Objective: To investigate the effect of covid‐19 BNT162b2 (Pfizer) vaccine on semen parameters among semen donors (SD). Methods: Thirty‐seven SD from three sperm banks that provided 216 samples were included in that retrospective longitudinal multicenter cohort study. BNT162b2 vaccination included two doses, and vaccination completion was scheduled 7 days after the second dose. The study included four phases: T0 – pre‐vaccination baseline control, which encompassed 1–2 initial samples per SD; T1, T2 and T3 – short, intermediate, and long terms evaluations, respectively. Each included 1–3 semen samples per donor provided 15–45, 75–125 and over 145 days after vaccination completion, respectively. The primary endpoints were semen parameters. Three statistical analyses were conducted: (1) generalized estimated equation model; (2) first sample and (3) samples' mean of each donor per period were compared to T0. Results: Repetitive measurements revealed −15.4% sperm concentration decrease on T2 (CI −25.5%–3.9%, p  = 0.01) leading to total motile count 22.1% reduction (CI −35% – −6.6%, p  = 0.007) compared to T0. Similarly, analysis of first semen sample only and samples' mean per donor resulted in concentration and total motile count (TMC) reductions on T2 compared to T0 ‐ median decline of 12 million/ml and 31.2 million motile spermatozoa, respectively ( p  = 0.02 and 0.002 respectively) on first sample evaluation and median decline of 9.5 × 10 6 and 27.3 million motile spermatozoa ( p  = 0.004 and 0.003, respectively) on samples' mean examination. T3 evaluation demonstrated overall recovery without. Semen volume and sperm motility were not impaired. Discussion: This longitudinal study focused on SD demonstrates selective temporary sperm concentration and TMC deterioration 3 months after vaccination followed by later recovery verified by diverse statistical analyses. Conclusions: Systemic immune response after BNT162b2 vaccine is a reasonable cause for transient semen concentration and TMC decline. Long‐term prognosis remains good.